Pengaruh Optimalisasi Teknologi Digital dalam Peningkatan Kualitas Pembelajaran Mahasiswa Manajemen Pendidikan Islam - Aisyara Agustin; Muhammad Munawir Pohan (UMSU, 2026)
The use of digital technology in higher education learning has become a strategic necessity, but its implementation has not always had an optimal impact on learning quality. This study aims to analyze the effect of optimizing digital technology on students' learning quality in the Islamic Education Management Study Program. The study employed a quantitative approach using a survey. The study population comprised 165 active students, and the sample was drawn using the Slovin formula. Data were collected using a Likert-scale questionnaire and analyzed using simple linear regression after satisfying tests of validity, reliability, normality, and linearity. The results showed that optimizing digital technology had a significant effect on student learning, with a significance value of 0.000 (p ≤ 0.05) and a positive regression coefficient of 0.460. The coefficient of determination indicates that optimizing digital technology accounted for 21.5% of the variance in learning quality, with the remainder attributable to factors outside the research model. These findings confirm that digital technology plays a vital role in improving the quality of learning. Still, its effectiveness is highly dependent on the implementation of strategies, lecturer competence, and institutional support. This study recommends integrating pedagogical and managerial approaches to digital technology to continuously improve the quality of learning in Islamic higher education.